A novel video‐assisted thoracoscopic approach for pectus excavatum surgical treatment in a dog. Issue 6 (20th June 2022) - Bobis Villagrà, Diego; Charlesworth, Tim M.
Abstract: Objective: To describe a novel, video‐assisted thoracoscopic surgery (VATS) approach used to treat pectus excavatum (PE) in a dog. Animals: A 5 month‐old, 5.1 kg, intact, female, Cockapoo. Study design: Case report. Methods: Clinical, imaging and surgical records of a dog with severe PE who underwent VATS‐assisted sternal cast placement were reviewed and reported. Treatment involved introduction of a mild pneumothorax and use of VATS, allowing direct visualization and therefore safe passage of circumsternal sutures as they were placed to reduce the risk of vascular/cardiac or pulmonary penetration and intraoperative complication in this patient. Results: Treatment involved introduction of a mild pneumothorax and use of VATS, allowing direct visualization and therefore safe passage of circumsternal sutures as they were placed to reduce the risk of vascular/cardiac or pulmonary penetration and intraoperative complications in this patient. The patient recovered well and had an excellent long‐term outcome with significantly improved vertebral index and frontosagittal index. Conclusion: This modified technique resulted in an excellent outcome and minimized the risk of intraoperative complications during the surgical procedure in a dog. Clinical significance: This novel VATS approach for PE correction may provide a useful technique to help reduce intraoperative risk during PE correction in dogs.